Differences of Enzymatic Activity During Composting and Vermicomposting of Sewage Sludge Mixed With Straw Pellets - Hanc, Ales; Dume, Bayu; Hrebeckova, Tereza (Frontiers in Microbiology, 2022)
With increasing efforts to treat wastewater, the amount of sewage sludge is increasing. One of the ways to deal with sewage sludge is its composting or vermicomposting. The study aims were focused on profiling eight hydrolytic enzymes by fluorescence method using a multifunctional modular reader, and studying the proportion of basic microorganism groups during composting and vermicomposting of sewage sludge mixed with straw pellets in several proportions (0, 25, 50, 75, and 100%). The greatest decrease in enzymatic activity occurred in the first half of composting and vermicomposting. After 4 months of these processes, the least enzymatic activity was observed in the sludge with 50% and also 25% straw addition, indicating that straw is an important means for the rapid production of mature compost from sewage sludge. Enzymatic activity was usually less in the presence of earthworms than in the control treatment, because some processes took place in the earthworm digestive tract. For the same reason we observed reduced enzyme activity during fresh feedstock vermicomposting than precomposted material. Final vermicompost from fresh feedstocks exhibited less microbial biomass, and few fungi and G- bacteria compared to precomposted feedstock. The enzymatic activity during composting and vermicomposting of sewage sludge and their mixtures stabilized at the following values: β-D-glucosidase 50 µmol MUFG/h/g dw, acid phosphatase 200 µmol MUFP/h/g dw, arylsulphatase 10 µmol MUFS/h/g dw, lipase 1000 µmol MUFY/h/g dw, chitinase 50 µmol MUFN/h/g dw, cellobiohydrolase 20 µmol MUFC/h/g dw, alanine aminopeptidase 50 µmol AMCA/h/g dw, leucine aminopeptidase 50 µmol AMCL/h/g dw. At these and lesser values, these final products can be considered mature and stable.